GREEN ECONOMY COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN SAMPAH DI KABUPATEN GARUT - Pupung Pundenswari; Riksa Raesalat; Septiani Nur Haliza; Safta Rijalul Sidiq (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
Waste management is one of the problems in Garut Regency. Obstacles in overcoming waste management, especially in terms of waste transportation. The waste that can be transported by DLH is only from 10 of the 42 existing sub-districts. The waste produced by the community reaches 350 tons/day and is not matched by sufficient transport fleets. So there needs to be cooperation between stakeholders so that waste management can be effective. Researchers conducted research with a qualitative descriptive method. The purpose of this study is to determine the application of Collaborative Governance in waste management in Garut Regency. The results of the study show that the dimensions of the Collaborative process 1) Inter-face dialogue have been carried out by DLH and stakeholders. 2) Build the trust that has been established by the government, namely by creating the Kang Raling and PUDING programs as a form of commitment to the Garut Regency Regulation concerning Strategy and household waste management. 3) Regarding Commitment to the process, DLH is currently in the process of intensively fostering some of the Communities from 6 sub-districts. 4) Common understanding between DLH and related stakeholders is still having difficulties with different perceptions, meaning that there is no good understanding of the shared vision. And 5) The achievement of the results shows that the community that has been fostered by Experts from DLH is able to process their waste independently.